Marandu grass management and supplementation on performance and methane mitigation of Nellore bulls - Valente, Andre Luis da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Canopy height and supplementation is the mainly strategies to increase animal production or area gain in system on pasture. However, some reporter diverge about the correct management in tropical forages, furthermore, the effect of supplementation with soybean differently available in rumen in pasture still inconclusively. By this sense, two trials were conducted to evaluate the effect of supplementation for young Nellore bulls grazing Brachiaria brizantha cv. Marandu with different sward height on herbage characteristics, dry matter intake, digestibility, animal performance and gain per area during the rainy season. Hundred and eight animal young Nellore bulls were used. Treatments corresponded to three different canopy height (15, 25 and 35 cm) when years where analyzed and the combined with sward height and supplementation with mineral salt, supplement with soybean grain or supplement with protect fat. The level of supplementation was 0.5% of BW. Pastures were fertilizer according to local recommendations following soil analysis plus 135 and 90 kg of nitrogen by urea during first and second year, respectively. Increase the canopy height increased herbage mass whilst decreased stocking rate. There was no difference in hand-plucked herbage CP, NDF and IVDMD concentration among treatments. Supplemented animals had higher DM intake and digestibility values of all nutrients except protein when compared to the control treatment. However, the supplements did not affect the production of CH4 expressed as g CH4/day. The increase in liveweight gain using either supplement caused a decrease in the production CH4/ kg product and g CH4/kg DMI. Considering that relation between animal performance and stocking rate, marandu pastures should be not be grazed below 20-cm stubble or above 30-cm for greater productivity. By other hand, supplementation with lipid of low ruminal degradation can increase performance with higher effect of protect fat source ...

O correto manejo do pastejo e o uso estratégico da suplementação são os principais caminhos quando se visa aumentar a produção animal e/ou o ganho de área no sistema a pasto. No entanto, dados divergentes sobre o correto manejo em forrageiras tropicais e o efeito da suplementação com soja diferente disponível no rúmen ainda são encontrados. Nesse sentido, três experimentos foram realizados para avaliar o efeito da suplementação de touros jovens da raça Nelore em pastagem de Brachiaria brizantha cv. Marandu manejado em diferentes alturas. No primeiro experimento os tratamentos consistiram de três alturas do dossel (15, 25 e 35 cm) do pasto e foram estudadas as características de forragem, consumo de matéria seca, digestibilidade, desempenho animal e ganho por área durante a estação chuvosa. Foram utilizados trinta e seis animais tourinhos Nelore. Aumentar a altura do dossel refletiu em aumento da massa de forragem, enquanto diminuiu a taxa de lotação. Não houve diferença na composição química de PB, FDN e concentração DIVMS entre os tratamentos. No segundo experimento, foi avaliado o efeito da suplementação (sal mineral; suplemento com gordura protegida; suplemento com soja grão) no desempenho e produção de metano de bovinos mantidos em pastos de Brachiaria brizantha cv. Marandu manejados a 25 cm. Animais suplementados apresentaram valores de consumo e digestibilidade superior para todos os nutrientes, exceto proteína quando comparado ao tratamento controle. No entanto, a suplementação não afetou a produção de CH4, expressos em g CH4 / dia. O aumento no ganho de peso vivo dos animais suplementados refletiu em diminuição na produção de CH4 / kg de produto e g CH4 / kg CMS. No terceiro experimento foi avaliado um fatorial 3x3 - três alturas do dossel (15, 25 e 35 cm) e três suplementos (sal mineral; suplemento com gordura protegida; suplemento com soja grão) no desempenho, consumo e ...
Keywords: Bovino; Suplementos dieteticos; Nelore (Zebu); Metano; Pastagens - Manejo; Methane